The Influence of Clay Minerals Towards Resistivity and Chargeability Value for Groundwater Interpretation - Sarip, Muhd Khairul; Madun, Aziman (Recent Trends in Civil Engineering and Built Environment, 2021)
Abstract: Electrical Resistivity Method (ERM) and Induced Polarization (IP) is suitable for geophysical technique to groundwater interpretation due to non-destructive methods. It is difficult in determining the precise identification or classification of soil beneath the surface. The purposes of this study is to measure the electrical resistivity and chargeability with different type of clay minerals such as Kaolinite, Illite and Montmorillonite, measure the electrical resistivity and chargeability for clay minerals with different moisture content, and develop the earth-material-resistivity-chargeability interpretation table. This study consists setting of laboratory using ABEM Terrameter LS2 with 4 electrode principle connected with soil box in order to determine the resistivity and chargeability value towards clay minerals. This study will develop the earth material-resistivity-chargeability interpretation table for groundwater purposes and increase the knowledge about the flow of groundwater. However, with the presence of different amounts of moisture content in clay minerals shows that the values were greatly responded which was slightly reduced the value of resistivity and chargeability. By comparing the results, it shows that the Kaolinite clay mineral has the highest value of resistivity and chargeability which is 40.8 Ωm and 1.59 ms respectively compare to Illite and Montmorillonite. In addition, when the samples added with different amounts of moisture content, the samples were tested from dry-moist-saturated-oversaturated condition, at some point the resistivity and chargeability values become constant because the samples passing the liquid limit value which means the samples passes from liquid state to plastic state. Hence, the result shows the influence and the importances of clay minerals toward resistivity and chargeability towards minerals for groundwater interpretation purposes.